Ant-cultivated Chaetothyriales in hollow stems of myrmecophytic Cecropia sp. trees – diversity and patterns. (October 2016) - Nepel, Maximilian; Voglmayr, Hermann; Blatrix, Rumsais; Longino, John T.; Fiedler, Konrad; Schönenberger, Jürg; Mayer, Veronika E.
Abstract: Five Cecropia tree species occupied by four Azteca ant species from Costa Rica and French Guiana were investigated to assess the diversity and host specificity of chaetothyrialean fungal symbionts. The ITS rDNA region of the symbiotic fungi was sequenced either from pure culture isolation, or from environmental samples obtained from ant colonies nesting in hollow stems of the Cecropia host plants. The investigation revealed six closely related OTUs of Chaetothyriales. Neither the four Azteca species nor the six fungal OTUs were associated with specific Cecropia species. In contrast, ants and fungi showed an association. Azteca alfari was associated with a particular OTU, and often contained only one. Azteca coeruleipennis, Azteca constructor and Azteca xanthochroa were associated with a different set of OTUs and often had multiple OTUs within colonies. Possible reasons for these differences and the role of the fungi for the Azteca - Cecropia symbiosis are discussed.